Poster presentation Tests for the field evaluation of Bti, Pyriproxyfen and S – Methoprene in Cyprus - Vasquez Christodoulou, Marlen (My University, 2026)
Vasquez MI, Violaris M, Hadjivassilis A, Wirth MC, Tests for the field evaluation of Bti, Pyriproxyfen and S – Methoprene in Cyprus, Poster presentation, International Conference on Urban Pests, Budapest, Hungary, 13-16 July 2008.